A A CONTENT ANALYSIS OF TEACHER’S MORPHOLOGICAL AWARENESS IN TEACHING PAST TENSE VERBS THROUGH YOUTUBE - Pitriyah; Dewanti, Ratna (LPPM Universitas Harapan Bangsa, 2024)
This study examines the teacher's morphological awareness in teaching English, specifically focusing on the past-tense verb forms. The analysis is based on a YouTube instructional video titled